Statistical evaluation of the effect of ultrasound on the synthesis of calcium phosphates - Tolaba, Angel G.; Pellizaro, Thales A. G. [UNESP]; Rodriguez-Chanfrau, Jorge E. [UNESP]; Guastaldi, Antonio C. [UNESP] (Biointerface Research Applied Chemistry, 2019)
Calcium phosphates are widely used materials in tissue engineering due to their biocompativility and bioactivity. They are present in the bone along with the hydroxyapatite, which facilitates its use as a bioceramic. The mechanical and biological properties of the material obtained in the synthesis process are determined by the size of the particles. There are different ways to decrease the particle size of the materials. Among the methodologies used is the application of ultrasonic radiation. The objective of this work was to statistically evaluate the influence of the ultrasonic application during the synthesis of different phases of calcium phosphates, as well as the type of drying. The particle size determination was performed by scanning electron microscopy. The statistical comparison was made using one way ANOVA. Previously, the hypotheses necessary to validate the model were evaluated. The results were interpreted through its implementation in a statistical software InfoStat (2017 version). The results allow us to conclude that the application of ultrasound during the synthesis process significantly influences the particle size. The type of drying had no significant influence on the particle size.
Keywords: Calcium phosphates; Particle size; Ultrasonic method; Statistical evaluation